2004
DOI: 10.1051/0004-6361:20035951
|View full text |Cite
|
Sign up to set email alerts
|

On the jet structure and magnetic field configuration of GRB 020813

Abstract: Abstract. The polarization curve of GRB 020813 is discussed and compared to different models for the structure, evolution and magnetisation properties of the jet and the interstellar medium onto which the fireball impacts. GRB 020813 is best suited for this kind of analysis for the smoothness of its afterglow light curve, ensuring the applicability of current models. The polarization dataset allows us to rule out the standard GRB jet, in which the energy and Lorentz factor have a well defined value inside the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 30 publications
3
59
0
1
Order By: Relevance
“…We refer to the companion paper by Lazzati et al (2004) for a detailed theoretical discussion and interpretation of the data reported in the present work.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We refer to the companion paper by Lazzati et al (2004) for a detailed theoretical discussion and interpretation of the data reported in the present work.…”
Section: Resultsmentioning
confidence: 99%
“…In the present paper we report an intensive polarimetric follow up of the GRB 020813 OA. In a companion paper Lazzati et al (2004) report a physical interpretation of the polarization data published in this study. 1 See http://www.mpe.mpg.de/∼jcg/grbgen.html…”
Section: Introductionmentioning
confidence: 83%
“…In the top panel the Lorentz factor of the ejecta is assumed to remain equal to that of the freshly shocked fluid just behind the forward shock (FS), while the middle panel is assumed to follow the Blandford & McKee (1976) self-similar solution (BM). The bottom panel is for a structured jet where the energy per solid angle drops as θ −2 outside of some small core angle (taken from Lazzati et al 2004). In this case P(t/t j ) is practically independent of θ obs .…”
Section: The Radio Flare and Its Polarisationmentioning
confidence: 99%
“…The observer line of sight must be within the beam (otherwise the GRB would be undetectable) but in general not perfectly aligned with the jet. This breaks the source-observer axi-symmetry, avoiding the cancellation of electric vectors created in different emitting regions (Lazzati et al 2004).…”
Section: Polarimetric Observations Of Grb Afterglows and Hypernovaementioning
confidence: 99%